AN APPLICATION OF HOTELLING’S T2 TEST FOR THE COMPARISON OF THE VISUAL-ACOUSTIC METHOD IN THE IDENTIFICATION OF INGESTIVE CATTLE BEHAVIOR - VIGAS, Valdemiro Piedade; VOLPI, Denise; ALVES, Fabiana Villa; SILVA, Giovana Oliveira; SARAIVA, Erlandson Ferreira (Brazilian Journal of Biometrics, 2020)
The bioacoustic method is an important tool for the identiﬁcation of the ingestive behavior of ruminants, especially in extensive production systems. This is mainly due to its potential to solve the deﬁciencies presented by the usual method, which is based on the visual observation of the animals. In this article, we present a study whose main objective is to evaluate the accuracy of the bioacoustic method over the visual method to record the macroactivity of grazing cattle ingestive behavior. The comparison of the methods is made in terms of a multivariate statistical approach based on the use of Hotelling’s T2 test. To verify the test performance in comparing the methods, we developed a simulation study using a resampling approach. The results show that the bioacoustic method can be an eﬀective alternative to the visual method, with the advantage of being a noninvasive method that also allows the analysis of the micro events of ingestive behavior.